Microstructural evolution during austempering of a ASTM A-532 CLASS III type high chromium white cast iron undergoing abrasive wear - Higuera-Cobos, Oscar Fabián; Bucurú-Vasco, Jeison; Loaiza-Patiño, Andrés Felipe; Monsalve-Arias, Mónica Johanna; Mesa-Grajales, Dairo Hernán (Universidad Pedagógica y Tecnológica de Colombia, 2017)
This paper studies the influence of variables such as holding temperatures and times during austempering of High Chromium White Cast Iron (HCWCI), with the following chemical composition: Cr 25 %, C 3 %, Si 0.47 %, Mn 0.74 % and Mo 1.02 %. The aim of the austempering was to modify the percentage of retained austenite and its correlation to abrasive wear resistance under different conditions.Microhardness tests, SEM-EDS and XRD were performed to determine mechanical properties, chemical composition, and type of carbides and microstructures present, respectively. The tests complied with the ASTM G-65 standard. Results showed that the best performance against abrasion was achieved for austempering at 450 ºC with holding time of 6 hours.